A Pesantren Education Curriculum Model for Students with Post-Rehabilitation Psychosocial Mental Disabilities (PPMD) at Ainul Yakin Islamic Boarding School, Yogyakarta - Triana Hermawati; Laelatul Badriah (International Journal of Post Axial: Futuristic Teaching and Learning, 2026)
Islamic Boarding School Education Curriculum Model for Post-Rehabilitation Students with Psychosocial Mental Disabilities (PDMP) at Ainul Yakin Islamic Boarding School, Yogyakarta. Yogyakarta: Master’s Program in Islamic Education, Universitas Alma Ata Yogyakarta, 2026. This study was motivated by the absence of an Islamic boarding school curriculum model specifically designed to accommodate the spiritual, psychological, social, and independence needs of post-rehabilitation students with psychosocial mental disabilities (PDMP). This study aimed to develop and examine the effectiveness of the Self Spiritual Akliah (SSA)-based Islamic Boarding School Education Curriculum Model at Ainul Yakin Islamic Boarding School, Yogyakarta. This study employed the Research and Development (R&D) method based on the Borg and Gall model. The research stages included preliminary studies, needs analysis, product development and validation, Focus Group Discussion (FGD), product revision, field testing, and the development of a validated curriculum model. Data were collected through observation, interviews, documentation, literature studies, expert validation, FGD, and pretest and posttest administered to 30 students with PDMP. The data were analyzed qualitatively and quantitatively using N-Gain analysis. The study produced an SSA Curriculum Model consisting of three dimensions: Self, Spiritual, and Akliah. The Self dimension focuses on independence and self-management; the Spiritual dimension strengthens faith, worship, morality, patience, gratitude, sincerity, and reliance on God; while the Akliah dimension develops thinking abilities, social skills, and adaptability. The model includes educational objectives, learning outcomes, learning materials, instructional strategies, activity programs, mentoring systems, and evaluation instruments. Expert validation and FGD results indicated that the model was feasible, relevant, and applicable. The effectiveness test showed an increase in the average score from 58.43 in the pretest to 83.10 in the posttest, representing an improvement of 24.67 points. The average N-Gain score was 0.60 or 60.45%, which was classified as moderate or moderately effective. A total of 10 students, or 33.33%, achieved a high improvement category, while 20 students, or 66.67%, achieved a moderate category, with no students in the low category. Therefore, the SSA Curriculum Model was moderately effective in improving the spirituality, independence, social skills, and adaptive readiness of students with PDMP in family and community life.